Perancangan Media Pembelajaran Hewan Berkaki Empat Berbasis Augmented Reality Untuk Siswa Paud Harapan Bunda Dengan Metode Design Thinking - Devi Fitriani; Ruly Dwi Arista; Heni Wulandari (CV. Hawari, 2025)
This study is to design an interactive learning media about four-legged animals based on Augmented Reality (AR) for students of PAUD Harapan Bunda. Conventional learning methods are often less effective in attracting the interest of early childhood learning, so innovation in learning media is needed. The Design Thinking approach is used in the development of this media, including the stages of Empathize, Define, Ideate, Prototype, and Test. The Empathize stage is carried out through observation and interviews with teachers and students to understand the needs and challenges of learning. The Define stage identifies the main problem, namely the lack of interesting and immersive media. At the Ideate stage, various AR learning media concepts are developed. Then, the Prototype stage involves building an AR application that allows students to see 3D models of four-legged animals in the real environment through mobile devices. The Test stage is carried out by direct trials on PAUD Harapan Bunda students to evaluate the effectiveness and ease of use of the media. The results of the study are expected to show that this AR learning media can significantly increase the motivation, understanding, and learning experience of PAUD Harapan Bunda students regarding four-legged animals.